Hubungan Stres Dengan Enuresis Pada Anak Usia Prasekolah - Natasya Afrina; Linda Adriani (Indonesia, 2019)
At the stage of growth and development of children under five, many problems faced by parents. One of them is the problem of urinating, namely Enuresis (wetting the bed). Enuresis is an unpleasant habit for parents. Bedwetting is an issue that is often discussed and there are differences of opinion regarding its occurrence and treatment. This study aims to determine the relationship between stress and enuresis in preschool children at Al Muna Kindergarten, Gampong Bireuen Meunasah Dayah, Bireuen Regency. This type of research is analytic research with a cross sectional approach. The population in this study were 64 students at Al Muna Kindergarten, Gampong Bireuen Meunasah Dayah, Bireuen Regency. The sampling technique in the study was carried out in total population. The study was conducted from January 14, 2019 to August 25, 2019. Data were collected by interview using a questionnaire that had been tested for validity and reliability at Zam-Zam Kindergarten on June 7, 2019 with Cronbach's alpha value of 0.954. . The results showed that the stress level of children in Al Muna Kindergarten, Gampong Bireuen Meunasah Dayah was mostly in the non-stress category, as many as 49 people (76.6%). Enuresis in preschool children at Al Muna Kindergarten, Gampong Bireuen Meunasah Dayah mostly did not experience enuresis, as many as 38 people (59.4%).